The effects of criminal justice pedagogy on student attitudes - Giacopassi, David J. (American journal of criminal justice, 1991)
To determine the effects of an introductory criminal justice course on the attitudes of students toward the police, questionnaires were given in the first week of the semester to 425 students enrolled in Introduction to Criminal Justice courses and to 301 students enrolled in Introduction to Sociology courses. The survey was then readministered in the final week of the semester. The data reveal that while significant initial differences existed in orientation among the various student groupings, there was no significant change in attitudes between the pretest and posttest measurements.